PEMBERDAYAAN MASYARAKAT MELALUI SOSIALISASI DAN PEMBENTUKAN KELOMPOK TERNAK MADU TRIGONA (TETRAGONULA CLYPEARIS) DI DESA REBAN MADANI LINGSAR - Nursari, Sumita; Suryana, I Gede Putu; Alfianti, Septia (Universitas Mataram, 2023)
Reban Madani Village is one of the expansion villages in the Batu Mekar area, Lingsar District, West Lombok Regency. Reban Madani Village is a village with a fairly large area of agricultural land, plantations and community forest areas and has several natural tourism sectors so that it has great potential to cultivate trigona honey bees. Trigona honey bee cultivation is one of the creative economy-based community empowerment efforts, which is expected to support and contribute to improving the community's economy in the Batu Mekar village area, especially Reban Madani. This activity aims to develop Trigona honey with business management by initiating the formation of a Trigona honey livestock group with the main step being outreach to the community in Reban Madani Village. With the initial goal of